Maternal mortality in the Maternity Hospital of Lima - Mascaro S., Pedro (2015)
205 maternal deaths occurred in the Maternity Hospital of Lima in the last five years from 1980 to 1984, a period in which there were 154.131 births was evaluated, giving a maternal mortality rate of 9.3 per 10,000 live births. Death occurred in 12% in adolescents and 29% in women over 35 years, 20% nulliparous and 34% multiparous large. The main direct cause of death was constituted, infection (34%), mainly due to septic abortion and endometritis, toxemia (22%) and hemorrhage (16%), indirect causes TB, heart disease, pulmonary embolism, mole and choriocarcinoma , totaling 22%.